The poetics of rhythm in compositional shifts - the Meccan surahs as an example - محلول حنان; مصطفى نمر (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The Qur’anic language is a language rich in influential rhythms, and the Qur’anic rhythm is mentioned at different levels that are in perfect harmony with the meanings, to constitute a manifestation of the miraculous nature of the Qur’an, Rhythm has a major role in expressing the meanings of the Qur’anic text. Its role was not limited to vocal harmony only, but it also had aesthetic and semantic value to contribute to achieving the formal and semantic coherence of the Qur’anic text. This research seeks to study a modern phenomenon in the Qur’anic text, which is the poetics of grammatical rhythm, by examining some of the positions of syntactic variation such as introduction, delay, deletion, and addition in examples of Meccan surahs in a manner consistent with grammatical rhythm, Because this rhythm is of great importance in shedding light on multiple aspects of the miraculous systems of the Qur’an, Due to the diversity of the Meccan surahs in their rhythms, a reflection of the diversity of positions between encouragement at times and intimidation at other times, The Meccan surahs were distinguished by their rapid rhythm and the prominence of their music to suit the nature of the speech.